Hubungan Muslim dan non-Muslim dalam Kerangka Inklusivisme - Rulyjanto Podungge (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2018)
When a society grows and the needs of its members increase, the relation between them and other people—who possess various primordial identities—will be impossibly avoided. This social relation will potentially bring about friction among different groups existed in the society. Islam has established a number of rules concerning the relationship of Muslims and other religious adherents. Although the regulations have been firmly settled, the controversy among the Muslims themselves—in dealing with their relation with the non-Muslims—is often inevitable. The issue of relation with other people of different religions has become contentiously debatable topic among the Muslim academics. The debate has subsequently brought about the emergence of different ideological inclinations within the Muslim society. This ideological preference emerges through such number of “appearances” as moderates, radicals, liberals, traditionalists, and modernists. Each group possesses its own perception along with its arguments about the issue. This article seeks to explain the pattern of Muslims and non-Muslims relation in the light of more moderate and contextual approach. This is so why that Muslims should constantly prioritize inclusive behavior and reciprocally sincere interreligious dialogue with their non-Muslim fellows.